THE EFFECT OF GOVERNANCE ON ECONOMIC GROWTH IN ASEAN COUNTRIES - -, Muhammad Mashduqi; Ahmad Ramadhan (Fakultas Agama Islam Universitas Islam Al-Azhar, 2025)
This study analyzes economic growth in 11 ASEAN countries (Indonesia, Malaysia, Singapore, Philippines, Myanmar, Brunei Darussalam, Cambodia, Laos, Thailand, Vietnam, Timor Leste) for the period 2018-2022 using the panel data analysis method with the Eviews 10 application. The focus of the research is to evaluate the effect of governance on economic growth, with indicators of Political Stability, Government Effectiveness, Regulatory Quality, Rule of Law, and Control of Corruption. Secondary data is obtained from the annual report of World Government Indicators (2023). The results showed that Political Stability, Regulatory Quality, and Control of Corruption had no significant effect on economic growth. This indicates that political stability, the government's ability to formulate policies, and regulations that support the private sector have not been able to directly influence economic growth in ASEAN countries. This research is quantitative in nature and contributes to the understanding of the relationship between governance and economic development in the ASEAN region.